METODE PENANAMAN NILAI MORAL UNTUK ANAK USIA DINI - Mukhamad Murdiono (Jurnal Kependidikan, 2008)
This study was intended to describe the instilling of moral valuesat assigned kindergartens of 'Aisyiyah Bustanul Athfal’ in YogyakartaCity. The description was expected to picture the method that influencedmoral education to be chosen for the appreciative instilling of earlychildhood. The subjects of the study consisted of teachers at fiveAisyiyah Bustanul Athfal (ABA) Muhammadiyah kindergartenscovering: TK ABA Gedongkiwo, TK ABA Karangkajen, TK ABAKarangkunthi, TK ABA Pandeyan II, and TK ABA Karanganyar. Datawere gathered by observation, interview, and documentation.Authenticity probing techniques were utilized as triangulation. Theresults indicated that methods of moral value education were: storytelling, play, field trip, singing, out bond, inuring, figure of speech,poem, and discussion. One method which was usually being utilized wasrelating and inuring. Instilling methods indicated that moral teachingapparently led to students’ behavioural change, from one inauspiciousto turning good. Faced constraints in performing moral point instillingcovered: its reducing of gnostic deep relates and its reducing media tobe utilized for deep relates, and inconsistencies which often happenedbetween what the teacher did at school and what other elders did athome of in the surrounding environments